Efektivitas Bermain Engklek yang Dimodifikasi dalam Peningkatan Kemampuan Eksplorasi Warna pada Anak Disabilitas Intelektual - Septiani, Annisa; Ardisal, Ardisal; Nurhastuti, Nurhastuti; Safaruddin, Safaruddin; Yuliana, Syari (Universitas Negeri Padang, 2025)
This study aims to determine the effectiveness of playing modified hopscotch in improving color exploration skills in children with mild intellectual disabilities. This study uses a quantitative approach with an experimental method of Single Subject Research (SSR) type A-B-A design on one subject of a fourth-grade child at SLB Negeri 1 Padang. The observed color exploration skills include the ability to show and group three basic colors (red, yellow, and blue). The results showed that the color exploration skills in the form of the ability to show and group basic colors from the baseline phase (A1) carried out during four meeting sessions obtained a percentage of 25%. In the intervention phase (B) the percentage was stable in the fifth to eighth meetings for showing basic colors at 100% and in the third to eighth meetings the percentage was stable at 100% for grouping basic colors. In the baseline session (A2) which was carried out during four meeting sessions had a stable percentage of 100%. Thus, playing modified hopscotch is proven to be effective in improving color exploration skills in children with mild intellectual disabilities.